THE REGULATION AND RECONCILIATION OF ABU BAKAR ASH-SHIDDIQ: STUDY THE HISTORICAL CYCLE MOVEMENT IBNU KHALDUN PERSPECTIVE - Fajariyah, Lukman (Jurnal Tamaddun: Jurnal Sejarah dan Kebudayaan Islam, 2023)
Leadership in a government is always inseparable from challenges. Life in the context of the nation under the government system is always dynamic. One of the roles and functions of a leader is to face these challenges internally and externally in solutive ways. Leaders are here to lead the people of a diverse nation, here leaders are required to be able to unify the vision. As represented by the caliph Abu Bakar Ash-Shiddiq in solving all challenges of the caliphate, such as the emergence of internal conflicts and defiance of the Arab people. This paper aims to explore the caliphate system of Abu Bakr after the Prophet’s death. This study uses a qualitative-descriptive research method using a historical approach and Ibn Khaldun’s theory of historical cycle motion. The findings of this study are that Abu Bakr’s persistence and firmness in governing can resolve all disobedience and rebellion and even he can make progress during his caliphate such as the expansion of Islamic territory, collection of verses of the Koran, and development of the bait al-mal.